2018
DOI: 10.2105/ajph.2018.304689
|View full text |Cite
|
Sign up to set email alerts
|

Reducing HIV-Related Health Disparities in the Health Resources and Services Administration’s Ryan White HIV/AIDS Program

Abstract: The Health Resources and Services Administration’s Ryan White HIV/AIDS Program (RWHAP) supports direct health care treatment and support services to more than 50% of all people living with diagnosed HIV in the United States. A critical goal of the RWHAP is to reduce HIV-related health disparities to help end the HIV epidemic. From 2010 through 2016, the RWHAP made significant progress reducing viral suppression disparities among client populations, particularly among women, transgender persons, youths, Blacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 8 publications
3
50
1
Order By: Relevance
“…Our finding that young MSM had lower odds of sustained viral suppression is consistent with national studies of the general population of PLHIV [7,9,[13][14][15]. A study of 33 United States jurisdictions with complete reporting of viral load tests found that in 2014, [13][14][15][16][17][18][19][20][21][22][23][24] year old PLHIV were more likely to have unsuppressed viral loads Fig. 1 Factors associated with sustained viral suppression among men who have sex with men.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our finding that young MSM had lower odds of sustained viral suppression is consistent with national studies of the general population of PLHIV [7,9,[13][14][15]. A study of 33 United States jurisdictions with complete reporting of viral load tests found that in 2014, [13][14][15][16][17][18][19][20][21][22][23][24] year old PLHIV were more likely to have unsuppressed viral loads Fig. 1 Factors associated with sustained viral suppression among men who have sex with men.…”
Section: Discussionsupporting
confidence: 83%
“…Our rate of sustained viral suppression among MSM (84.4%) was higher than that reported in previous national studies [7,[13][14][15][16]. This may be due to a significant upward trend in sustained viral suppression overtime nationwide [13,17] and among PLHIV enrolled in the Ryan White Program [18] since previous studies used data from 2009 to 2016 and our study used 2017 data. Furthermore, previous studies have focused on the general population of PLHIV.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Such collaborations have also played a crucial role in the development and scale-up of systems of care for persons living with HIV. The federally-funded Ryan White HIV/AIDS Program (RWHAP), which now provides direct health care and support services for over half of all people diagnosed with HIV in the US [21], was first authorized some 9 years after the epidemic initially emerged [22]. The record shows that during the early years of the American epidemic, federal government was "slow to develop targeted programs to provide care" for persons sickened by the virus [22].…”
mentioning
confidence: 99%